Como desenhar e escrever um protocolo de pesquisa clínica em Cosmiatria - Bagatin, Ediléia; Miot, Hélio Amante [UNESP] (FapUNIFESP (SciELO), 2013)
Cosmetic Dermatology is a growing subspecialty. High-quality basic science studies have been published; however, few double-blind, randomized controlled clinical trials, which are the major instrument for evidence-based medicine, have been conducted in this area. Clinical research is essential for the discovery of new knowledge, improvement of scientific basis, resolution of challenges, and good clinical practice. Some basic principles for a successful researcher include interest, availability, persistence, and honesty. It is essential to learn how to write a protocol research and to know the international and national regulatory rules. A complete clinical trial protocol should include question, background, objectives, methodology (design, variable description, sample size, randomization, inclusion and exclusion criteria, intervention, efficacy and safety measures, and statistical analysis), consent form, clinical research form, and references. Institutional ethical review board approval and financial support disclosure are necessary. Publication of positive or negative results should be an authors' commitment. © 2013 by Anais Brasileiros de Dermatologia.
How to design and write a clinical research protocol in Cosmetic Dermatology
Keywords: Clinical protocols; Clinical trial; Comparative study; Cosmetics; Epidemiologic research design; Research design; cosmetic; isotretinoin; placebo; sunscreen; actinic keratosis; clinical practice; clinical protocol; clinical research; comparative study; cryotherapy; dermatology; drug efficacy; drug safety; elasticity; evidence based medicine; human; humidifier; hydration; methodology; mucocutaneous candidiasis; photoaging; randomized controlled trial (topic); review; skin surface